A Dual Liquidity Model for Emerging Markets - Caballero, Ricardo J; Krishnamurthy, Arvind (American Economic Review, 2002)
The last few years have seen a significant re-evaluation of the models used to analyze crises in emerging markets. Recent models typically stress financial constraints or distorted financial incentives. While this certainly represents progress, these models share a weakness with the earlier work: neither is uniquely about emerging markets. Adaptations of the Mundell-Fleming model represent Argentina as a Belgium with larger external shocks. Likewise, emerging market models of financial constraints are adaptations of developed economy ones with tighter financial constraints. In our work, we have advocated a model which distinguishes between the financial constraints affecting borrowing and lending among agents within an emerging economy, and those affecting borrowing from foreign lenders. This 'dual liquidity' model offers a parsimonious description of the behavior of firms, governments, and asset prices during financial crises. It also provides prescriptions for optimal policy responses to these crises.